(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
Autopsy plays a significant role in determining the cause of both natural and unnatural deaths. Identifying the cause of death becomes more challenging when it occurs suddenly and rapidly, particularly in cases involving trauma, whether known or unknown, or in a case of concealed underlying pathology. The role of cardiac inhibitory reflex as a potential cause of death remains debatable. This case report describes a fatal incident of such nature. The reasons for such neurocardiogenic vasovagal shock can be attributed to sudden shock or strong emotions and injury to specific areas such as the carotid sinus, various plexuses, testicles, and serous membranes. Even minor trauma to these areas can lead to sudden death. This case report describes a 43-year-old male who was assaulted by his neighbour as a result of a long-standing feud and died almost immediately after minor trauma to the neck and chest.